France : Selected Background Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper analyzes a broad range of price and nonprice indicators to assess developments in the international competitiveness of the French economy during the 1980s and early 1990s. The paper provides a brief review of conceptual issues concerning the competitiveness indicators used in this study. Developments in conventional price- and cost-based indicators, both at the aggregate and bilateral levels, are reported. The paper discusses additional price- and quantity-based measures of competitiveness, and also examines the labor market dynamics and economic policy of France.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet